The Impacts of Strategic Orientation and Knowledge Management on Firms’ Performance of SMEs in Surabaya - Sunyoto, Hadi Kusuma; Sendy, Sendy; Lay, Felicia Cheryl (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
The importance of SMEs as the driver of economic growth globally has become more crucial over recent decades because of the constantly changing business environment. SMEs especially in Indonesia have supported the government in fighting the unemployment rate. Nevertheless, the common problem of SMEs is sustaining their businesses because of ineffective operations and exploring competitive advantage. The objective of this study is to identify the performance of SMEs in Surabaya City, Indonesia. Three strategic orientations: market orientation, technology orientation, entrepreneurial orientation, and knowledge management were used to test firms’ performance. This study applies the multiple linear regression analysis, classic assumption test, and purposive sampling technique. The findings of this study encompass that technology orientation, entrepreneurial orientation, and knowledge management variables significantly influence firms’ performance. Only the market orientation variable was found not significant on firms’ performance.